Assessment of Technology, Organization, and Environment Readiness for Integrated Hypertension Management: Penilaian Kesiapan Teknologi, Organisasi, dan Lingkungan untuk Pengelolaan Hipertensi Terpadu - Pradnyantara, I Gusti Agung Ngurah Putra; Faidah, Nurul (Universitas Muhammadiyah Sidoarjo, 2025)
Hypertension is one of the most prevalent chronic diseases in Indonesia, affecting 34.1% of adults over 18 years according to the 2018 National Health Survey. Effective hypertension management requires an integrated health information system for continuous monitoring. The Indonesian government, through Ministry of Health Regulation No. 24/2022, mandates hospitals to implement Electronic Medical Records (EMR) and integrate them with the SATUSEHAT national platform. This study aims to analyze the readiness of Dharma Yadnya General Hospital Denpasar to develop an integrated hypertension management module within the EMR system using the Technology-Organization-Environment (TOE) framework. A qualitative approach was employed through in-depth interviews, observations, and document review. Eleven informants participated, representing medical record officers, IT staff, physicians, and hospital management. Findings indicate that from the technological dimension, the hospital has basic infrastructure such as servers, internal networks, and a fully implemented EMR since 2024, though a dedicated hypertension module is absent. From the organizational dimension, management and staff show strong commitment and readiness to adopt the new system with proper training, while limited IT human resources and manual hypertension SOPs remain barriers. From the environmental dimension, government regulations, the SATUSEHAT program, and vendor support are identified as key external drivers. The study concludes that the hospital has strong potential to implement an EMR-based hypertension management module with recommendations on hardware procurement, IT capacity building, and SOP integration.